Absences, presences and unintended consequences in debates about masculinities and social change: a reply to Christofidou. Issue 3 (3rd July 2021) - Roberts, Steven; Elliott, Karla; Ralph, Brittany
ABSTRACT: This article offers a reply – and an alternative perspective – to Andria Christofidou's recent contribution to this journal, which critically engages with debates on men, masculinities and social change. We first suggest that understanding change requires us to go beyond pitting theoretical frameworks against one another, and we highlight work that has done this. Second, as our main point, we argue that when bringing in intersectionality as a theory or concept, CSMM scholars must maintain the spirit of the foundational thinking of the idea, such that inequalities are uncovered, highlighted and challenged. We also stress that marginalised men, in the Global South but also the Global North, must be included in the story of social change. While our response is stimulated by Christofidou's article, our contention applies to a wide range of thinking in CSMM.